Visibility, framing and importance: Images of the EU in Japan and South Korea - Natalia Chaban; Christian Elias Schneider; Richard Malthus (The Copenhagen Journal of Asian Studies, 2009)
Addressing an under-researched theme of international images and perceptions of the EU, this paper scrutinizes the framings of the Union endorsed in the news media and expressed by the general public in the two East Asian OECD countries – Japan and South Korea. Conclusions indicate that the EU’s importance and presence is often underestimated in the region, and frequently seen in terms of ‘economic muscle’ only. The empirical data comes from a trans-national comparative research project, sponsored by the Asia-Europe foundation (ASEF). The research framework is interdisciplinary, drawing resources from critical discourse analysis, media and image studies, EU scholarship and political science